Homophily and peer-consumer behaviour in a peer-to-peer accommodation sharing economy platform. Issue 2 (25th January 2022) - Cho, Sunyoung; Park, ChongWoo; Lee, Frank
ABSTRACT: Peer-to-peer (P2P) accommodation is considered as an important subsector of the 'sharing economy'. P2P sharing economy (SE) platforms bring mostly individual actors called 'peers' together to create value. In general, interactions among peers in P2P SE platforms are considered novel and social with communal feelings such as friendliness and social satisfaction (Perren and Kozinets 2018, Lateral Exchange Markets: How Social Platforms Operate in a Networked Economy) and some research attention has been paid to peer interaction dynamics on P2P accommodation platforms in recent years. This study employs homophily, a potential user interaction dynamic but rarely studied in the context of SE platforms, and investigates its impact on peer-consumer behaviour in a P2P accommodation platform. We also examine homophily drivers in the context of accommodation sharing platforms. Our results suggest that homophily does contribute to peer-users' consumption intention through trust and attitude, and that ethnicity and gender, two strong homophily factors identified in the literature, do not have statistically significant effects on homophily in this context. However, qualitative analysis of open-ended questions suggests that other homophily factors may be more influential in the accommodation sharing economy context. We believe that this study makes a meaningful contribution by expanding our understanding of peer-users' interaction dynamics in the context of accommodation sharing platforms.